2006
DOI: 10.1162/qjec.2006.121.2.635
|View full text |Cite
|
Sign up to set email alerts
|

Tying Odysseus to the Mast: Evidence From a Commitment Savings Product in the Philippines

Abstract: We designed a commitment savings product for a Philippine bank and implemented it using a randomized control methodology. The savings product was intended for individuals who want to commit now to restrict access to their savings, and who were sophisticated enough to engage in such a mechanism. We conducted a baseline survey on 1777 existing or former clients of a bank. One month later, we offered the commitment product to a randomly chosen subset of 710 clients; 202 (28.4 percent) accepted the offer and opene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

68
898
7
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,280 publications
(983 citation statements)
references
References 22 publications
(16 reference statements)
68
898
7
10
Order By: Relevance
“…While hard commitments have real economic penalties for failure, soft commitments rely on the psychological consequences of not sticking to one's commitments (Bryan et al, 2010). Examples of external devices include saving accounts that restrict withdrawals (Ashraf et al, 2006), Christmas saving clubs, informal bets, and voluntarily putting one's name on a list of people who are banned from gambling in casinos (Thaler and Sunstein, 2008). As a commitment device to reduce one's impulsive wine consumption, one can take only a limited amount of money and no credit card to the restaurant.…”
Section: Nudging Ethical Consumer Behaviormentioning
confidence: 99%
“…While hard commitments have real economic penalties for failure, soft commitments rely on the psychological consequences of not sticking to one's commitments (Bryan et al, 2010). Examples of external devices include saving accounts that restrict withdrawals (Ashraf et al, 2006), Christmas saving clubs, informal bets, and voluntarily putting one's name on a list of people who are banned from gambling in casinos (Thaler and Sunstein, 2008). As a commitment device to reduce one's impulsive wine consumption, one can take only a limited amount of money and no credit card to the restaurant.…”
Section: Nudging Ethical Consumer Behaviormentioning
confidence: 99%
“…Indeed, past research has demonstrated that people value mechanisms that prevent their future selves from making unwise decisions such as procrastinating (Ariely and Wertenbroch 2002), undersaving (Ashraf et al 2006, Beshears et al 2011, smoking cigarettes (Giné et al 2010), failing to achieve workplace goals (Kaur et al 2010), and giving in to repeated temptations in the laboratory (Houser et al 2010). Study participants have expressed a willingness to use "commitment devices" such as placing money in restrictive accounts that prevent premature savings withdrawals (Ashraf et al 2006, Beshears et al 2011; self-imposing deadlines with associated late penalties to prevent procrastination on coursework (Ariely and Wertenbroch 2002); and placing money on the line for forfeiture if they fail to quit smoking, exercise, or lose weight (Halpern et al 2012, John et al 2012, Royer et al 2012, Volpp et al 2008.…”
Section: Utility Utilitymentioning
confidence: 99%
“…Study participants have expressed a willingness to use "commitment devices" such as placing money in restrictive accounts that prevent premature savings withdrawals (Ashraf et al 2006, Beshears et al 2011; self-imposing deadlines with associated late penalties to prevent procrastination on coursework (Ariely and Wertenbroch 2002); and placing money on the line for forfeiture if they fail to quit smoking, exercise, or lose weight (Halpern et al 2012, John et al 2012, Royer et al 2012, Volpp et al 2008.…”
Section: Utility Utilitymentioning
confidence: 99%
See 1 more Smart Citation
“…If one of the sexes is more impatient or time inconsistent than the other then consumption and savings could differ substantially during a lifetime. 1 With their empirical paper, Ashraf et al (2006) showed that saving behavior can indeed be affected by time inconsistency. In detail, they find that women are, or at least consider themselves to be, more time inconsistent when studying savings among bank clients in the Philippines.…”
Section: Introductionmentioning
confidence: 99%